-2(b-4)=-(b-8)

Simple and best practice solution for -2(b-4)=-(b-8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -2(b-4)=-(b-8) equation:


Simplifying
-2(b + -4) = -1(b + -8)

Reorder the terms:
-2(-4 + b) = -1(b + -8)
(-4 * -2 + b * -2) = -1(b + -8)
(8 + -2b) = -1(b + -8)

Reorder the terms:
8 + -2b = -1(-8 + b)
8 + -2b = (-8 * -1 + b * -1)
8 + -2b = (8 + -1b)

Add '-8' to each side of the equation.
8 + -8 + -2b = 8 + -8 + -1b

Combine like terms: 8 + -8 = 0
0 + -2b = 8 + -8 + -1b
-2b = 8 + -8 + -1b

Combine like terms: 8 + -8 = 0
-2b = 0 + -1b
-2b = -1b

Solving
-2b = -1b

Solving for variable 'b'.

Move all terms containing b to the left, all other terms to the right.

Add 'b' to each side of the equation.
-2b + b = -1b + b

Combine like terms: -2b + b = -1b
-1b = -1b + b

Combine like terms: -1b + b = 0
-1b = 0

Divide each side by '-1'.
b = 0

Simplifying
b = 0

See similar equations:

| x^2+1-11=0 | | 4xn+2=10+2n | | 20w^2+10w+40=0 | | 16x^2-96x+4y^2+8y=-84 | | 96j+245=53 | | log(2)18=x | | 12x+9-5x^2=0 | | -8x+9x=-2 | | 5n+1=2n+3 | | 6.7x-3.4=16.7 | | 5x-9+4x=3x+30 | | 7p-23=-17+8p | | 2v+7=5v+4 | | 45=360+x | | 2r-16=-6+4r | | 4g+20=10g+5 | | Y=8sec(5x) | | 2(x-7)-9=-23 | | 5(3x+2)=7 | | 3n+2=1n+12 | | (x+10)(x+5)+(x+-3)(x+12)+(x+11)(x+30)=106 | | 2x^4=35 | | 1n+9=4n+3 | | -16x^2+240x+20=0 | | 2.5x+2.4=7.8 | | 4m-8+2m=2(3m-4) | | 3x^2-3=2x-1 | | 3n+6=4n+1 | | 5-21=2a | | solvex+0.08(60)=0.20(60+x) | | 3(x+5)=x+3+2x | | Sen(2x)+sen(4x)=0 |

Equations solver categories